Transpersonal Caritas Relationship: A new concept from the unitary caring science framework of Jean Watson - Delgado Galeano, Mayut; Ibáñez Alfonso, Luz Eugenia; Villamizar Carvajal, Beatriz; Durán de Villalobos, María Mercedes (Investigación y Educación en Enfermería, 2024)
Objective. To analyze deeply the concept of the transpersonal caring relationship as the core of the theory of Caring Science proposed by Jean Watson. To present a historical evolution and to introduce the Transpersonal Caritas Relationship construct. Methods. Methodological Study to support the central concept measured by the Watson Caritas patient instrument. We designed a focus group with four nursing scholars to develop the "Transpersonal Caritas Relationship" construct. We recount the history of the concept of the transpersonal caring relationship, then analyze this concept in terms of Watson's theory. We reviewed the concept with Dr. Jean Watson, presented her with the construct, and discussed our considerations. Results. This article introduces a transitional adaptation of the concept of transpersonal relationship to Caritas’ transpersonal relationship. Transpersonal Caritas Relationship is the foundation of evolved Caritas nursing, recognizing that mutual caring affects the universal field we all belong to Caritas' consciousness and action affect the energy field when the nurse relates with the other, making it possible to awaken the compassionate heart, which is the foundation of Evolved Caritas Nursing Universal love and in this way evolve to the Caritas consciousness that allows recognizing the other with loving kindness in the practice of careful. This is the proposed central concept measured in the caring approach using the Watson Caritas Patient. Conclusion. This article introduces a transitional adaptation of the concept of transpersonal relationship to the Caritas transpersonal relationship, which is the foundation of Caritas Evolved Nursing.